Synthesis, characterization and catalytic studies of bimetallic heteronuclear complexes for the reduction of nitroaromatic compounds. Issue 5 (4th May 2023) - Adimula, Vincent O.; Tella, Adedibu C.; Owalude, Samson O.; Oladipo, Adetola C.; Olayemi, Victoria T.; Adeniyi, Emmanuel; Ismail, Bushra; Mumtaz, Amara; Khan, Asad M.
Abstract: Four mixed-ligand complexes were prepared and formulated as [Ln(H2 OBA)(H2 PZDC)] and [Ln(H2 OBA)(H2 PDC)] {Ln = La & Gd; H2 OBA = 4, 4-oxybisbenzoic acid; H2 PDC = 2, 3-pyridinedicarboxylic acid; H2 PZDC = 2, 3-pyrazinedicarboxylic acid}. The complexes were modified by a nickel/cobalt impregnation method to generate bimetallic complexes 1–8 . Fourier transform infrared (FTIR) spectroscopy analysis of the bimetallic complexes indicated that the carboxylate coordinated to the lanthanide ion via the OH- group while the Ni 2+ and Co 2+ ions were preferentially bonded to the nitrogen donor ligand via the N- group. Complete catalytic reduction of 4-nitrophenol to 4-aminophenol by the Ni@ complexes gave a maximum reduction time of 37 minutes for complex 1 while complex 7 gave a reduction time of 21 minutes. The rate constants were observed to increase with an increase in temperature up to 50 °C for complexes 3, 5, and 7.